Mosquitoes and their control - Becker, Norbert; Petrić, Dušan; Boase, Clive; Lane, John; Zgomba, Marija; Dahl, Christine; Kaiser, Achim (Springer US Imprint: Springer, 2003)
Mosquitoes and their Control presents a multitude of information on bionomics, systematics, ecology and control of both pestiferous (nuisance) and disease vectors in an easily readable style providing practical guidance and important information to both professional and layman alike. Ninety-two species and subspecies belonging to 8 genera and 18 subgenera are described in the fully illustrated identification keys to adult females and males and fourth-instar larvae. The illustrated keys are followed by a detailed description of the morphology, biology and distribution of each species including over 700 detailed drawings